2021
DOI: 10.1587/transele.2020sui0002
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication Process for Superconducting Digital Circuits

Abstract: This review provides a current overview of the fabrication processes for superconducting digital circuits at CRAVITY (clean room for analog and digital superconductivity) at the National Institute of Advanced Industrial Science and Technology (AIST), Japan. CRAVITY routinely fabricates superconducting digital circuits using three types of fabrication processes and supplies several thousand chips to its collaborators each year. Researchers at CRAVITY have focused on improving the controllability and uniformity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Superconducting digital circuits based on Josephson junctions [1][2][3][4] can thus achieve high operating speed and low switching energy, making them a key technology for developing superconducting information systems, such as microprocessors [5][6][7][8], neuromorphic computing systems [9,10], and reversible computers [11,12]. To realize large-scale, high-performance superconducting systems, fabrication processes have been continuously improved [13][14][15] and many types of circuit design tool have been developed [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting digital circuits based on Josephson junctions [1][2][3][4] can thus achieve high operating speed and low switching energy, making them a key technology for developing superconducting information systems, such as microprocessors [5][6][7][8], neuromorphic computing systems [9,10], and reversible computers [11,12]. To realize large-scale, high-performance superconducting systems, fabrication processes have been continuously improved [13][14][15] and many types of circuit design tool have been developed [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several research groups have reported successful demonstrations of large-scale, energy-efficient superconductor digital circuits [8][9][10], which indicates the high robustness, as well as the high energy efficiency, of superconductor logic families. Note that these demonstrations were supported by recent advances in fabrication technology for superconductor integrated circuits [11][12][13].…”
Section: Introductionmentioning
confidence: 82%
“…We designed test circuits using the AIST 10 kA cm −2 Nb high-speed standard process (AIST-HSTP) [36,37] to demonstrate the frequency synchronization of two SFQ oscillators. We used a three-dimensional inductance extraction tool Induc-tEX [38] was used for precise inductance design.…”
Section: Methodsmentioning
confidence: 99%